The Local Culture Based Learning Materials and Reading Interest of English Students IAIN Padangsidimpuan - Eka Sustri Harida; Sri Rahmadhani Siregar; Addini Hayatunnuha Rahmadani (Linguanusa : Social Humanities, Education and Linguistic, 2024)
Introduction to The Problem: Reading interest is important for the students to learn; and reading materials is also important. Purpose: The purposes of this study were to identify students' reading interest and to explore the effectiveness of local-culture based learning materials to the students' interest of reading of English Department IAIN Padangsidimpuan. Design/methods/approach: It was done by using quasi-experimental research, with pre-test and post-test design. Data were collected by using reading interest questionnaires, and analysed by using SPSS 20 to know means, standard deviation, and independent t-test. Findings: After analysing, the students' reading interest in pre-test was 43.58 and in post-test was 60.11. Using local culture-based learning materials to students' reading interest has significant effect, because the value of significance of t-test value (0.000) smaller than 0.05, and hypotheses was accepted. Research implications/limitations: Thus, it was suggested to the lecturers to be more creative to use learning materials. It will be better if the learning materials given are having relationship to the students' life and culture in order to make them activating their schemata in reading, because it helps the students in comprehend what they learn.